Motivations of online gaming and identification of avatar predict internet gaming disorder’s symptoms among youth in Malaysia - Bong, Wei Jian; Teh, Emilia Yi Wen; Yon, Da Yaw (2019)
There is a need to further study on Internet Gaming Disorder’s symptoms in Malaysia context due to its limited research. Furthermore, the study of multiplayer online battle arena (MOBA) games has received inadequate scholarly attention in Malaysia, and also pathological online gaming behaviour is growing among youth in Malaysia. The purpose of the study is to examine the predictive effect of achievement motivation, social motivation, immersion motivation, and identification of avatar on Internet Gaming Disorder’s symptoms. Crosssectional research design was employed and purposive sampling method was applied in selecting participants who are (1) MOBA gamers; (2) between 18 to 29 years old; (3) have 12 months gaming experience and above. 781 respondents were recruited and 706 of respondents were used in actual study analysis. Instruments used included Internet Gaming Disorder Scale–Short-Form, Player-Avatar Identification Scale, and Online Gaming Motivations Scale. Current results presented that immersion motivation and identification of avatar are significant positive predictors of Internet Gaming Disorder’s symptoms, and social motivation is a significant negative predictor of Internet Gaming Disorder’s symptoms, however, achievement motivation did not significantly predict Internet Gaming Disorder’s symptoms. Self-Determination Theory and Social Identity Theory were employed in the study. Mental health professionals can design their interventions to educate youth in Malaysia to adopt healthy coping mechanisms to deal with daily stress, to teach youths the ways to form offline social support and also form meaningful self-identity in the real world.